Sealed bag stack video - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Bag stacks are a familiar feature of grain storage systems in developing countries. The conventional means of preserving grain in such bag stacks involves fumigation under a gas-tight sheet, with the gases methyl bromide or phosphine, and surface...